Vegetative propagation of azalea (Rhododendron simsii Planch) - Fernandes, F.M.; Fernandes, P.D.; Mattos, J.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
Effects of Exuberone and planting seasons. This work refers to the study of the development of azalea (Rhododendron simsii, planch) cuttings, in the four different seasons of the year and the effect off phytolohormone (Exuberone) applied by the slow method, in eight different concentrations. The results, obtained showed that the best period for the rooting of azalea cuttings, was the and of spring (ovember), independently of the application of Exuberone. The phytohormone effects were variable in the same season and between seasons. The period less favourable for rooting was the end of winter (September).